Komunikacja pośrednia w organizacji. Interwencja papier – ołówek a zmiana zachowań pracowniczych na bardziej proaktywne - Ślebarska, Katarzyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The main goal of the study was to verify the effectiveness of indirect communication technics in organizational trainings. An intervention aimed at improving proactive coping was used in the study. The intervention was designed as booklet. Data were collected from N = 172 organizational entrants within a longitudinal evaluation design (one pretest and double posttest). The results revealed the positive effect of the prepared RAAC intervention training with controlling the level of general self-efficacy.
Keywords: indirect organizational communication; intervention; proactive coping